Transdziedzinowość – retoryczność – cyfryzacja. W stronę tekstów transdziedzinowych i eksplozji strukturalnej - Szczęsna , Ewa (Przestrzenie Teorii, 2020)
The article analyses the agency of transgression and transcendence at the domain level. It characterizes the specificity of this process and points to factors that influence its intensification (especially the development of digital technologies). The text presents the effects of this process – the impact on the way cultural texts and their structures exist. The article examines the rhetorical dimension of a trans-disciplinary nature, the effect of which is the creation of trans-disciplinary texts. It proves the thesis that in the interaction between disciplines a structural explosion takes place, which leads to the creation of new textual figures and structures and the formation of new types of texts. These issues are illustrated using specific examples of trans-disciplinary texts.